Chemical composition, antioxidant properties, and antifungal activity of wild Origanum elongatum extracts against Phytophthora infestans - Hari, Amal; Echchgadda, Ghizlane; Darkaoui, Fatima-Azzahra; Taarji, Noamane; Sahri, Nihad; Sobeh, Mansour; Ezrari, Said; Laasli, Salah-Eddine; Benjelloun, Meryem; Lahlali, Rachid (Frontiers in Plant Science, 2024)
Introduction: Phytophthora infestans, the causative agent of the late blight disease, has gained notoriety for its destructive potential, leading to substantial losses in potato yields. Although conventional systemic fungicides have been shown to be effective in controlling plant pathogens, growing environmental concerns have prompted the need for more integrated disease management approaches. Hence, in this study, the effectiveness of wild Origanum elongatum extracts as biopesticides was explored in controlling P. infestans and potentially mitigating its devastating impact in planta.The aerial parts of O. elongatum were subjected to sequential extraction using water, hexane, chloroform, and methanol. The obtained extracts were tested in vitro by the poisoned food procedure for their capacity to obstruct P. infestans growth and to defeat potato blight severity in vivo. The phyto-contents and the antioxidant activities, were spectrophotometrically determined in all extracts and the phytoconstituents of the most active extract (methanolic extract) were profiled via HPLC-PDA-MS/MS.In vitro, the complete inhibition rate of the P. infestans was obtained using the methanolic extract at 5 mg mL -1 , followed by the hexane and the chloroform extracts at 10 mg mL -1 . Interestingly, complete inhibition of the pathogen was achieved upon the application of the aqueous extract at 10 mg mL -1 . The aqueous extract at 25 mg mL -1 reduced P. infestans severity rate to 27.25 % while the methanolic extract at 20 mg mL -1 led to the lowest severity rate. Moreover, the hexane and chloroform extracts impaired the pathogen severity to 50 and 41 % using 20 mg mL 1 , respectively The TPC and TFC in the extracts were variable with high concentrations detected in the methanolic extract with 485.42 mg GAE g -1 and 58.24 mg QE g -1 , respectively. In addition, the methanolic extract showed the highest antioxidant activities, while the chloroform extract exhibited the lowest activity. LC-MS/MS analysis of the methanol extract revealed 56 components from diverse classes. These include organic acids, phenolic acids, flavonoids, tannins, and coumarins.Conclusions: These findings suggest that O. elongatum could be investigated as a potential source of antifungal compounds targeting different phytopathogens.